Very High Movement Speed in a Hitting Action Affects Interjoint Coordination But Not Spatial Accuracy. - Okazaki, Victor Hugo Alves; Teixeira, Luis Augusto (Journal of Applied Biomechanics, 2025)
Performance of ballistic movements to drive a ball toward a spatial target in different sports requires high movement speed associated with spatial accuracy. In this investigation, we compared target hitting movements performed from very low to very high movement speeds with the purpose of assessing the effects on movement accuracy and variability. Participants were 16 young men, naive for the experimental task. The task consisted of sliding a handle over a flat surface to hit a moveable disc, with the aim of driving it toward a spatial target. Kinematic analysis indicated that the high and very high movement speeds induced the lowest peak and contact velocity variabilities of the handle displacement and elbow extension. Assessment of interjoint coordination between the shoulder, elbow, and wrist indicated higher relative phase values in very high speed compared with lower movement speeds. As the main outcome, we found no evidence for effects on either spatial accuracy or variability of the disk displacement toward the target due to increment of movement speed. Our findings support the conclusion that ballistic skills can be performed with high movement speeds while keeping spatial accuracy and variability unchanged.